Determination of tumour biomarkers homovanillic and vanillylmandelic acid using flow injection analysis with amperometric detection at a boron doped diamond electrode - Němečková-Makrlíková, Anna; Navrátil, Tomáš; Barek, Jiří; Štenclová, Pavla; Kromka, Alexander; Vyskočil, Vlastimil (Analytica chimica acta, 2019)
A new method for the simultaneous determination of two tumour biomarkers, homovanillic (HVA) and vanillylmandelic acid (VMA), using flow injection analysis (FIA) with amperometric detection (AD) at a commercially available boron doped diamond electrode (BDDE) was developed. It was found that this method is suitable for the determination of HVA (in the presence of VMA) and VMA (in the presence of HVA) in optimum medium of Britton-Robinson buffer (0.04 mol L-1, pH 3.0). Calibration dependences consist of two linear parts for both biomarkers, the first one being in the concentration range from 1 to 10 μmol L-1 and the second one from 10 to 100 μmol L-1 (with obtained LODs 0.44 μmol L-1 for HVA and 0.34 μmol L-1 for VMA, respectively). To minimize any negative effects related to the passivation of the working electrode, suitable cleaning pulses (+2.4 V for 30 s) were imposed on the working electrode after each measurement. An attempt to use FIA with multiple pulse amperometric detection to determine both analytes in one run was not successful. Changing potentials in short intervals in multiple pulse detection probably results in mutual interaction of analytes and/or products of their electrochemical oxidation, thus preventing the application of this approach.
Keywords: nádorové biomarkery; Oxidation-Reduction; Electrochemical Techniques; kyselina homovanilová; oxidace-redukce; Biomarkers, Tumor; Flow Injection Analysis; Homovanillic acid; elektrody; Homovanillic Acid; Vanillylmandelic acid; průtoková injekční analýza; Boron; kyselina vanilmandlová; Vanilmandelic Acid; limita detekce; Electrodes; Diamond; Tumour biomarkers; bor; Boron doped diamond electrode; elektrochemické techniky; diamant; Limit of Detection; Flow injection analysis